Fundamentals of public communication campaigns - Matusitz, Jonathan Andre, 1976- (Wiley Blackwell, 2023)
"Public communication campaigns are found everywhere and it is nearly impossible to elude them in our modern-day environment of traditional communication and social media. By and large, a campaign is a comprehensive and organized attempt at shaping the behavior, attitude, or decision-making status within a community of people. It is a strategic course of action carried out during a specific time limit and for a precise outcome. A public communication campaign consists of a set of coordinated messages or other communicative efforts aimed at accomplishing predetermined goals and objectives: to sway a high number of people's beliefs, attitudes, and behaviors. Atkin (1981) defines "public communication campaign" as a method that uses "promotional messages in the public interest disseminated through mass media channels to target audiences." Public communication campaigns tend to be waged by state or non-state actors who seek to inform or affect behaviors in large audiences through an organized set of communication processes. They are designed with two phases in mind. The first phase generates awareness about a certain topic. Thus, a campaign has a purpose; the desired outcomes can be diverse ranging from individual level cognitive impacts to social or systemic change. The second phase uses that awareness to instill behavior change and shape the thoughts or actions of the audience; it is typically aimed at a large audience. "Large" is an important concept here because it helps differentiate campaigns from interpersonal persuasive endeavors by one or a few person that seek to influence a handful of others"--